1990
DOI: 10.1002/ajim.4700180605
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and morbidity among army chemical corps Vietnam Veterans: A preliminary report

Abstract: Nearly 1,000 men serving in Army Chemical Corps units in Vietnam between 1965 and 1971 were responsible for the mixing and application of herbicides, riot control substances, and burning agents. Information on Vietnam service was obtained from military records of 94% of this cohort. Follow-up for vital status on December 31, 1987, was conducted using Department of Veterans Affairs (VA), military, National Death Index, U.S. Internal Revenue Service, and Social Security Administration records. Cause-specific obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…In the original VA Chemical Corps Study [Thomas and Kang, 1990], study participants were identified from morning reports for all Army Chemical Corps detachments assigned to Vietnam between 1966 and 1971. All persons from those morning reports were included, regardless of occupational specialty.…”
Section: Selection Of Study Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the original VA Chemical Corps Study [Thomas and Kang, 1990], study participants were identified from morning reports for all Army Chemical Corps detachments assigned to Vietnam between 1966 and 1971. All persons from those morning reports were included, regardless of occupational specialty.…”
Section: Selection Of Study Subjectsmentioning
confidence: 99%
“…An excess mortality from diseases of the digestive system was observed but not believed to be associated with Agent Orange exposure. In 1990, the Department of Veterans Affairs (VA) conducted a mortality and morbidity follow-up of 894 persons who served in Army Chemical Corps units in Vietnam between 1966and 1971[Thomas and Kang, 1990. Compared to the U.S. male population, statistically significant excesses of digestive disease deaths and motor vehicle accidents were observed for the Army Chemical Corps personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The most potent dioxin congener, 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), has been declared a human carcinogen by the IARC for all cancer sites based on sufficient evidence in animals, a convincing mechanistic model, and limited evidence in humans (10). For non-Hodgkin's lymphoma specifically, there is compelling evidence of increased risk resulting from exceptionally high exposures in occupational settings (11)(12)(13) and following an accidental industrial release in Seveso, Italy (14); there have been few studies of the effects of dioxins within the general population. Furans and coplanar PCBs exhibit similar toxicologic properties as dioxin through their potential to bind to the arylhydrocarbon receptor, whereas other (noncoplanar or standard) PCBs elicit biological responses that are primarily mediated through other pathways (15).…”
Section: Introductionmentioning
confidence: 99%
“…Both the CDC and the VA studies looked broadly at Vietnam service, without a special focus on Agent Orange exposure (although some VA studies focused on Chemical Corps veterans 21,22 ). In contrast, a third study, the Air Force Health Study, focused specifically on approximately 1200 Ranch Hand veterans directly involved in herbicide distribution and 1300 comparison veterans.…”
Section: Agent Orange Exposurementioning
confidence: 99%